An Analysis of Phishing Attacks: Information Technology Security: Cybercrime and Its Solutions - Abid, Noman (CV. Multi Kreasi Media, 2024)
Phishing is one of the most primary and persistent threats when it comes to cybersecurity, and is grounded on deception tropes which try to pry information from individuals or organizations or get unauthorized access to their systems. Phishing, which is discussed in this review, circles around every trick the criminals employ, the collection of intelligence by the attackers and the countermeasures which may be applied to contain the attacks. There are different types of phishing such as spear-phishing, phishing have become popular so have AI-based attacks which shows that one method is not sufficient anymore. The organizations hence need to implement several layers of defense like; Information user awareness, two-factor or mult-factor technique, superior email filtering technique and rigid enforcement of the email verification procedures like SPF, DKIM and DMARC. New chances will be expected from the methods like Machine Learning, Behavioural Biometrics, and Block Chain for efficient detection and control of the phishing. Zero Trust security model, which only periodically validates each access request to reduce the vulnerability of successful cyber-attacks has notes on how to use it. Likewise, there is more sharing of intelligence and working across industry in real time very central in tackling phishing threats. At present, there is a heightened appreciation of better user security, the dangers that require anticipative measures, continuous monitoring, and popularity of use. This paper emphasizes that combat against phishing requires a systematic and timely approach that incorporates technology and user awareness as well as organizational backing. As with the assistance of following what has been described here as best practices and solutions, one and everyone and every company may decrease the probability of being spoofed and the consequences of such spoofing.